2007
DOI: 10.1245/s10434-006-9320-5
|View full text |Cite
|
Sign up to set email alerts
|

Change of E-Cadherin by Hepatocyte Growth Factor and Effects on the Prognosis of Hypopharyngeal Carcinoma

Abstract: Background: Hepatocyte growth factor (HGF) is known to induce scattering in various epithelial cells, and E-cadherin plays important roles in the maintenance of cell-cell adhesion. However, the mechanisms surrounding these actions are not fully understood. Therefore, we examined how HGF affects the expression and distribution of E-cadherin. In addition, we observed the relationship between prognosis and modulation of E-cadherin by HGF in hypopharyngeal carcinoma.Methods: Tumor tissues from 66 patients with hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…Particularly, cMET expression was found to be statistically more frequent in The following cut-offs were used: cMET \20 % vs. C20 %, Notch3 \80 % vs. C80 %, pMAPK \40 % vs. C40 % Notch3 has a borderline significance as a predictive biomarker in CUP squamous carcinomas compared to adenocarcinomas and carcinomas. This observation is in line with reports about the emerging role of HGF and its receptor in the pathogenesis of squamous carcinomas [23,24], possibly through down-regulation of E-cadherin and subsequent promotion of epithelial-mesenchymal transition (EMT) phenotype [25,26], as confirmed by our group (cMET down-regulates E-cadherin, unpublished data). Similarly, a link was revealed between squamous histology and Notch3 overexpression, which suggests a common pathogenetic mechanism between cMET and Notch3 in CUP, probably through EMT [27].…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, cMET expression was found to be statistically more frequent in The following cut-offs were used: cMET \20 % vs. C20 %, Notch3 \80 % vs. C80 %, pMAPK \40 % vs. C40 % Notch3 has a borderline significance as a predictive biomarker in CUP squamous carcinomas compared to adenocarcinomas and carcinomas. This observation is in line with reports about the emerging role of HGF and its receptor in the pathogenesis of squamous carcinomas [23,24], possibly through down-regulation of E-cadherin and subsequent promotion of epithelial-mesenchymal transition (EMT) phenotype [25,26], as confirmed by our group (cMET down-regulates E-cadherin, unpublished data). Similarly, a link was revealed between squamous histology and Notch3 overexpression, which suggests a common pathogenetic mechanism between cMET and Notch3 in CUP, probably through EMT [27].…”
Section: Discussionsupporting
confidence: 92%
“…(I) HT-29 human colorectal cancer cells were cultured until subconfluency, serum-free fresh medium exchanged and a 12-hour conditioned medium (CM) was prepared and (II) added 50% diluted in fresh medium to primary cultured hepatocytes and stellate cell-derived myofibroblasts obtained from hepatic tissue fragments resected for treatment purposes from patients with hydatid cyst, and approved by our Ethics Committee. Next (III), new conditioned media were obtained from untreated and HT-29-CM-treated hepatocytes and hepatic myofibroblasts and added 50% diluted in fresh medium to HT-29 colon cancer cells may facilitate the mobility of cancer cells required for dissemination, while its overexpression by colon cancer cells at hepatic metastasis sites herein detected, is consistent with previous studies on E-Cadherin regulation in epithelial cancer cells [100,101], and may indicate reactivation of an epithelial cell differentiation program needed for secondary tumor growth. Osteopontin (SPP1) is a hypoxia-regulated extracellular matrix protein that has been proposed as lead marker for tumor progression and metastasis in colon cancer and hepatocellular carcinoma [102,103].…”
Section: Hepatic Microenvironment-dependent Colon Cancersupporting
confidence: 80%
“…18,21,23,[58][59][60][61][62] In addition, hepatocyte growth factor/scatter factor (HGF/SF) expression has been associated with E-cadherin ectodomain shedding and increased invasiveness of cancer cells. 63 The protease(s) responsible for E-cadherin cleavage in CC-RCC has not been identified. However, it has been shown that VHL regulates the expression of tissue inhibitors of metalloproteinases (TIMPs) and MMP2 and 9, and their deregulation have been shown to promote branching morphogenesis in cells devoid of functional VHL.…”
Section: Discussionmentioning
confidence: 99%